Rutting and fatigue behavior of neat and nanomodified asphalt mixture with SiO2 and TiO2 - Ahmed Mahir Mohammed; Alaa H. Abed (Alexandria Engineering Journal, 2024)
Modern asphalt technology has adopted nanomaterials as an alternative option to assert that asphalt pavement can survive harsh climates and repeated heavy axle loading during service life and prolong pavement life. This work aims to elucidate the behavior of the modified asphalt mixture fracture model and assess the fatigue and Rutting performance of Hot Mix Asphalt (HMA) mixes using the outcomes of indirect Tensile Strength (IDT), Semicircular bend (SCB) and rutting resistance; for this, a single PG (64−16) nanomodified asphalt binder with 5 % SiO2 and TiO2 have been investigated through a series of laboratory tests, including: Resilient modulus, Creep compliance, and tensile strength, SCB, and Flow Number (FN) to study their potential role of these nanomaterials to improve the rutting characteristics and fatigue life of wearing asphalt mixture at different temperatures. The outcome of this study revealed the positive role of these materials in enhancing mixture IDT characteristics, fracture energy, and viscoelastic deformation component of crack propagation; on the other hand, at higher temperatures, the modified mixture exhibited a superior performance in reducing the permanent deformation of asphalt mixture with SiO2 followed by TiO2 as compared to neat asphalt mixture.